Ideal Nasal Preferences: A Quantitative Investigation with 3D Imaging in the Iranian Population - Kiarash Tavakoli; Amir K. Sazgar; Arman Hasanzade; Amir A. Sazgar (Archives of Plastic Surgery, 2023)
Background Though in facial plastic surgery, the ideal nasal characteristics are defined by average European-American facial features known as neoclassical cannons, many ethnicities do not perceive these characteristics as suitable.